2017
DOI: 10.7287/peerj.preprints.3354v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

umx: Twin and Path-based Structural Equation Modeling in R

Abstract: Structural equation modeling (SEM) is an important research tool, both for pathbased model specification, common in the social sciences, and also matrix-based models in heavy use in behavior genetics. We developed umx to give more immediate access, concise syntax and helpful defaults for users in these two broad disciplines. umx supports development, modification, and comparison of models, as well as both graphical and tabular output. The second major focus of umx, behavior genetic models, is supported via fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…This single factor accounted for 39.8% of variance. Testing fit of a 1-factor model using structural equation modeling using OpenMx (Neale et al, 2015) and umx (Bates, 2014;Bates, Neale, & Maes, 2017) packages in R (R Core Team, 2016). This indicated that a model with one modification (a covariance between brain storming and group checkers) fit well (χ²(113) = 4.2, p = 0.380; CFI = 0.993; TLI = 0.984; RMSEA = 0.043).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This single factor accounted for 39.8% of variance. Testing fit of a 1-factor model using structural equation modeling using OpenMx (Neale et al, 2015) and umx (Bates, 2014;Bates, Neale, & Maes, 2017) packages in R (R Core Team, 2016). This indicated that a model with one modification (a covariance between brain storming and group checkers) fit well (χ²(113) = 4.2, p = 0.380; CFI = 0.993; TLI = 0.984; RMSEA = 0.043).…”
Section: Resultsmentioning
confidence: 99%
“…Empathizing has no effect on the latent group-IQ factor, but is allowed to affect one or more single test scores. Each of these models was built and compared using OpenMx (Neale et al, 2015) and umx (Bates, 2014;Bates et al, 2017) packages in R (R Core Team, 2016). Empathizing is also part-dependent on IQ, but has zero effect on group-IQ.…”
Section: Four Alternative Models Of the Origins Of Group-iq Performancementioning
confidence: 99%
“…All analyses were completed using R (R Core Team, 2016) and umx (Bates, 2014;Bates, Neale, & Maes, 2017). Standardized effect sizes are reported to aid interpretability and incorporation into subsequent meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The first step involved the vectorization of functional connectivity matrices' lower triangle ("Shen" -35,778 edges; "Gordon" -55,278 edges). The heritability analyses were performed using the umx package 43 , after regressing out the effect of age and sex using 'umx_residualize'.…”
Section: Heritability Analysesmentioning
confidence: 99%
“…Multivariate ACE models were fitted with bootstrapping. The Cholesky's ACE model 43 used in this framework allocates observed phenotypic variability into three factors: A (heritabilityh 2 ), C (shared environmentc 2 ) and E (measurement error or external sources of variabilitye 2 ) in a multivariate fashion. In our iterative multivariate approach, 10 edges were randomly selected and used as covariates to fit an ACE model (umxACEv).…”
Section: Heritability Analysesmentioning
confidence: 99%